IPO Volatility in Indian Markets - Bansal, Yash; Desai, Anand N. (Indian Journal of Finance, 2012)
Raising money by offering Initial Public Offering (IPO) has proven to be an effective mechanism for firms. A firm with the help of underwriters fix the issue price usually, ’leaving enough on the table’. This IPO underpricing has been well documented by various researchers across the globe, including the authors, in the Indian context. This phenomenon and the absence of any trading history make it difficult to determine the fair price of the stock. In case of markets being fully efficient, the listing price should reflect the fair value, and the price should be fairly stable after that. The authors challenge the notion of existence of strong form of efficiency in the Indian markets by providing empirical evidences on volatility and volume trading. To reduce this volatility, the authors have proposed several mechanisms such as use of anchor investors, price band on listing day, strengthening derivatives market and alternative method to book building in determining issue price.